Atrazine induces endoplasmic reticulum stress‐mediated apoptosis of T lymphocytes via the caspase‐8‐dependent pathway. Issue 8 (9th January 2015) - Lee, Eun‐Jin; Jang, Youngsaeng; Kang, Kwonyoon; Song, Da‐Hyun; Kim, Rihyun; Chang, Hee‐Won; Lee, Dong Eil; Song, Claire Ka‐Eun; Choi, Bongkun; Kang, Min‐Ji; Chang, Eun‐Ju
ABSTRACT: Atrazine (ATR) is one of the most commonly applied broad‐spectrum herbicides. Although ATR is well known to be a biologically hazardous molecule with potential toxicity in the immune system, the molecular mechanisms responsible for ATR‐induced immunotoxicity remain unclear. In this study, we found that the immunotoxic properties of ATR were mediated through the induction of apoptotic changes in T lymphocytes. Mice exposed to ATR for 4 weeks exhibited a significant decrease in the number of spleen CD3 + T lymphocytes, while CD19 + B lymphocytes and nonlymphoid cells were unaffected. ATR exposure also led to inhibition of cell growth and induction of apoptosis in human Jurkat T‐cells. Importantly, ATR triggered the activation of caspase‐3 and the cleavage of caspase‐8 and PARP, whereas it did not affect the release of cytochrome c from the mitochondria in Jurkat T‐cells. In addition, ATR activated the unfolded protein response signaling pathway, as indicated by eIF2 α phosphorylation and CHOP induction. Our results demonstrate that ATR elicited an immunotoxic effect by inducing ER stress‐induced apoptosis in T‐cells, therefore providing evidence for the molecular mechanism by which ATR induces dysregulation of the immune system. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 998–1008, 2016.